Kesalahan Umum yang Dialami Siswa Kelas 2 dalam Operasi Hitung dan Cara Mengatasinya (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Errors in basic arithmetic operations are frequently encountered among second-grade elementary students. These issues arise from various factors, including a lack of conceptual understanding, misinterpretation of place value, and limited use of supportive learning media. This article aims to identify common types of mistakes in addition, subtraction, multiplication, and division encountered by second-grade students. It also explores effective strategies that teachers and parents can implement to help students overcome these difficulties. Through contextual learning approaches, the use of concrete teaching aids, and personalized guidance, students can develop a deeper understanding of mathematical concepts and reduce the frequency of errors in solving arithmetic problems. This study is expected to serve as a practical reference for teachers, parents, and education practitioners in improving mathematics instruction at the early primary level.